Class I histone deacetylases regulate p53/NF-κB crosstalk in cancer cells - Schäfer, Claudia; Dietrich, Sascha (Cellular signalling, 2017)
The transcription factors NF-κB and p53 as well as their crosstalk determine the fate of tumor cells upon therapeutic interventions. Replicative stress and cytokines promote signaling cascades that lead to the co-regulation of p53 and NF-κB. Consequently, nuclear p53/NF-κB signaling complexes activate NF-κB-dependent survival genes. The 18 histone deacetylases (HDACs) are epigenetic modulators that fall into four classes (I-IV). Inhibitors of histone deacetylases (HDACi) become increasingly appreciated as anti-cancer agents. Based on their effects on p53 and NF-κB, we addressed whether clinically relevant HDACi affect the NF-κB/p53 crosstalk. The chemotherapeutics hydroxyurea, etoposide, and fludarabine halt cell cycle progression, induce DNA damage, and lead to DNA fragmentation. These agents co-induce p53 and NF-κB-dependent gene expression in cell lines from breast and colon cancer and in primary chronic lymphatic leukemia (CLL) cells. Using specific HDACi, we find that the class I subgroup of HDACs, but not the class IIb deacetylase HDAC6, are required for the hydroxyurea-induced crosstalk between p53 and NF-κB. HDACi decrease the basal and stress-induced expression of p53 and block NF-κB-regulated gene expression. We further show that class I HDACi induce senescence in pancreatic cancer cells with mutant p53.
Available online 9 November 2016
Gesehen am 11.09.2018